Pemanfaatan Potensi Lokal Ubi Jalar dan Labu Kuning untuk Meminimalisasi Penggunaan Tepung Gandum dalam Pembuatan Aneka Kue - Andi Nur Faidah Rahman; Mulyati M. Tahir; Jumriah Langkong (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Takalar District is one of the areas in South Sulawesi with its superior product that is sweet potato. Sweet potato production in this area is quite abundant but has not been utilized properly. This activity aimed to utilize the abundant local potential in making various cakes to minimize the use of wheat flour. The method used was counseling and training. The activity was carried out in Tala, Sombalabella Village, Pattalassang Subdistrict, Takalar District. Participants amount are 25 peoples consisting of cake traders and housewives who are not economically productive. The activity was carried out with two sessions, that is material present and practice. Based on the results of participant's questionnaires, there was an increase in the knowledge of the participants up to 80, the participants already knew how to utilize the potential of sweet potatoes and pumpkin in their area to have higher economic value. In addition there was an increase in the skills of the participants up to 92 in processing sweet potatoes and pumpkin into a variety of cakes such as donuts, panada, and fried bread as well as participants skilled in packaging products with vacuum and non-vacuum plastic packaging. Community service activities from the economic side can increase people's income, and from the health side can add the nutritional value of the community from that various cakes produced.